Optimalisasi Pelayanan Publik Digital di Provinsi Sumatera Barat: Kebijakan Integrasi Sistem dan Partisipasi Masyarakat - Endri, Elfi (Journal of Current Research in Management, Policy, and Social Studies, 2026)
Digital public service transformation in West Sumatra Province has not yet reached its optimal potential. Despite concrete commitments outlined in Regional Regulation No. 6 of 2021 (RPJMD) and the Governor's Decree on Leading Program Performance, implementation remains hindered by several critical issues. These challenges include ICT infrastructure disparities, low digital literacy among both officials and the public, weak inter-departmental (OPD) system integration, and limited public participation. This study aims to critically analyze these obstacles and formulate strategic policy alternatives to accelerate a sustainable digital transformation. Utilizing William N. Dunn’s policy analysis framework, this research evaluates three policy alternatives based on criteria of effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that Alternative 3,